ANALISIS YURIDIS SENGKETA KEPEMILIKAN TANAH GARAPAN DI DESA HELVETIA KECAMATAN LABUHAN DELI KABUPATEN DELI SERDANG (STUDI PUTUSAN MAHKAMAH AGUNG NO. 537.K/Pdt/2011) - YUSRIANSYAH RAMADHAN (PREMISE LAW JURNAL, 2016)
A dispute over land rights commonly occurs in society. It  has occurred in Helvetia Village, Labuhan Deli Sub-District, Deli Serdang District based on the Supreme Court’s Ruling No.537.K/Pdt/2011.The problems of research were whether or not the renunciation of rights and the compensation for tilled land were legitimate based on the judge’s consideration and the legal consequence for the tilled land ownership; and, how about the settlement for the tilled land dispute based on the Supreme Court’s Ruling No. 537.K/Pdt/2011 which had given a legal certainty to the owner. This research applied descriptive analysis design which was aimed to provide a systematical, factual, and accurate description. A descriptive analytical research describes, reviews, explains, and analyzes laws both theoretically and practically in the research results. Keywords: Dispute, Ownership, Tilled Land